A Comparison of Hilbert and Fast Fourier Transform Techniques for Reciprocating Motors - Abdillah Fatkhurrokhman; Subekti Subekti; Nur Indah (JTTM : Jurnal Terapan Teknik Mesin, 2024)
Human existence has been significantly impacted by the growth of information and technology, particularly in relation to the requirement for effective mobility. But as a car ages, symptoms that affect its performance and safety start to show. These symptoms are a serious worry. Interference with car parts, such coils, is one issue that can have a major effect on driving safety and performance. Vibration analysis techniques have been successful in addressing this problem by detecting damage to different car parts. With the intention of comprehending piston motor vibration characteristics at different rotational speeds. The piston motor was used to collect vibration data at three distinct speeds: 900 rpm, 1500 rpm, and 3500 rpm. Both the Hilbert approach, which offers profound insight into frequency energy, and an FFT analyzer, which produces clear frequency spectrum information, were used in the analysis. The findings demonstrated that vibration characteristics changed in response to variations in reciprocating motor speed. On the other hand, the average frequency energy tends to remain constant across a range of speeds, suggesting that the features of reciprocating motors may be complicated and not very affected by variations in speed. According to this study, different perspectives on the vibration characteristics of piston motors operating at different speeds can be gained by utilizing vibration analysis techniques like FFT and Hilbert. Improved comprehension of this phenomenon could have a significant impact on maintenance initiatives and performance analysis of vehicles. To fully understand the complexity of vibration characteristics in reciprocating motors at various speed conditions, more research will be needed